Agent-Based Modeling of Vertical Tsunami Evacuation in Enggano Island, Indonesia: Route Dynamics, Shelter Capacity, and Behavioral Performance - Defina Yuandita; Hardiansyah; Lindung Zalbuin Mase; Khairul Amri; Fepy Supriani (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Enggano Island is situated above the southern segment of the Sunda megathrust, making it highly vulnerable to earthquake and tsunami hazards. In remote coastal villages, such as Kaana, the lack of adequate evacuation infrastructure presents significant challenges for disaster risk reduction. This study aims to evaluate tsunami evacuation strategies using an agent-based modeling approach implemented in a three-dimensional simulation environment. A purposive sampling survey involving 83 residents was conducted to collect socio-demographic data, tsunami awareness, preparedness levels, and evacuation preferences. These inputs were used to calibrate agent behavior and movement patterns to reflect realistic community dynamics in the simulation. The model simulates multiple evacuation configurations to examine survival rates and evacuation times under different spatial layouts, building distributions, and shelter capacity assumptions. Results show that horizontal evacuation via a single inland route leads to severe congestion and low survival outcomes, with only 8.2% of agents reaching safety within ten minutes. In contrast, the addition of vertical evacuation buildings significantly enhances evacuation performance, yielding survival rates above 90% under all conditions. Even when shelter capacity is limited to 70% of its full design, over 93% of agents are still able to evacuate successfully, although with increased delays. Vertical-only evacuation produces stable performance with average completion times of approximately five minutes. These findings emphasize the importance of integrating vertical shelters in strategic locations, optimizing route accessibility, and adapting building capacity to physical and demographic constraints. This study contributes to tsunami risk mitigation planning by offering empirical insights into evacuation dynamics in isolated island environments such as Enggano Island, Indonesia.